Clinicopathological characteristics and prognosis of hepatitis B associated membranous nephropathy and idiopathic membranous nephropathy complicated with hepatitis B virus infection - Ruiqiang Wang (Nature Portfolio, 2021)
Abstract The main objective of this study is to analyze the clinical and pathological features and prognosis of patients with Hepatitis B associated membranous nephropathy (HBV-MN) and idiopathic membranous nephropathy (IMN) complicated with hepatitis B virus (HBV) infection. This study will provide more basis for diagnosis and prognosis evaluation. A total of 50 patients with HBV-MN were included in this study. 56 IMN patients complicated with HBV infection diagnosed during the same period formed the control group. Parameters including blood routine, urine routine and plasma levels of albumin (ALB), serum creatinine (SCR), blood urea nitrogen (BUN), urea acid (UA), total cholesterol (T-CHO), triglycerides (TG), complement C3 and C4, glutamic pyruvic transaminase (ALT), glutamic pyruvic transaminase (AST), 24-h urinary protein quantification (24 h-TP), renal phospholipase A2 receptor (PLA2R) and HBV related markers during the hospitalization and outpatient follow-up study period were collected for all the patients. The proportion of male patients was high in both groups. The average age of the HBV-MN group was 37.2 ± 14.187 years old, it was younger compared with the IMN group (P = 0.003). Nephrotic syndrome was the major clinical manifestation among patients. There was no significant difference between the two groups in the levels of anemia, microscopic hematuria, renal dysfunction, liver dysfunction, liver cirrhosis. The level of serum C3 and C4 in the HBV-MN group was lower compared with the IMN group (P = 0.002, P = 0.014). In the HBV-MN group, serum HBV markers were negative in 6 (12%) patients, 4 patients (8%) were positive for PLA2R in serum, and 5 patients (10%) were positive for PLA2R in renal tissue. Stronger IgG1 and C1q and weaker IgG4 staining were found in HBV-MN group renal tissues (P = 0.003, P = 0.025, and P = 0.001, respectively). There were no statistical differences compared with serum and renal PLA2R between HBV-MN and IMN groups (P = 0.098, P = 0.109). During the 1-year follow-up, there was no significant difference in complete remission rate between the two groups (P = 0.7739). Renal biopsy is crucial to diagnose HBV-MN. IgG subtypes in the HBV-MN group were mainly IgG1 deposition, while those in IMN complicated with HBV infection group were mainly IgG4 deposition. When HBV-associated antigen and PLA2R are present in renal tissue, lower level of serum C3 and C4, high intensity of renal C1q and IgG1 is more supportive of HBV-MN. The positive of PLA2R in serum and renal tissue in differentiating HBV from IMN complicated with HBV infection remains to be discussed.